(untitled) (Религиски дијалог и соработка, 2022)
Religious personal laws of different religious communities essentiallygovernmarriage, divorce and other family-related matters in India. In this land of religiouspluralism, there have always been many cases of interfaith marriages. TheIndianChristian Marriage Act 1872 (ICMA) is arguably the only Indian personal lawin theorythatprovides legal means to solemnise interfaith marriage. It also mandates solemnisationof all marriages under its form where one of the parties to a marriage contractisaChristian under pain of invalidity. Specifically, Canon law of the Church under theICMA,1872 in the context of the Indian personal law system allows interfaith marriages, i.e.between Catholics and non-Christians provided the demands of the laware fulfilled. Therequirements of certain conditions from prospective interfaith couples, however, havebecome contentious in light of the principles of religious freedomand personal choice.In the wake of anti-conversion laws also called ‘Love Jihad’ laws in many Indianstates,solemnising interfaith marriage according to Canon law appears also legally ill advised.These challenges necessitate a common marriage law outside religious personal laws.Inorder to achieve this objective, the paper uses comparative research method(internal-external comparison) to compare and evaluate two legal orders. Consequently, thepaperidentifies, the Special Marriage Act, 1954 of India as providing such a facility for interfaithmarriage irrespective of religion or belief, but this optional secular lawis not well knownand has limitations. Therefore, harmonising the provisions of Canon lawand theoptionalsecular law of marriage (external comparison) is necessary to provide legal safeguardstointerfaith couples and to ensure religious freedom and personal choice.